Isothermal crystallization and melting behavior of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Singh, R. P. (Thermochimica Acta, 2009)
The effect of layered double hydroxide (LDH) nanolayers on the crystallization behavior of polypropylene (PP) was studied based on the preparation of nanocomposites by a melt intercalation method. The isothermal crystallization kinetics and subsequent melting behavior of PP/LDH hybrids were studied with differential scanning calorimetry (DSC), polarized optical microscopy (POM), and wide-angle X-ray diffraction (WAXD). Studies revealed that the LDH promoted heterogeneous nucleation, accelerating the crystallization of PR The Avrami equation successfully describes the isothermal crystallization kinetics of PP/LDH hybrids and signifies heterogeneous nucleation in crystal growth of PR The varying values of Avrami exponent (n) and half crystallization time (t(1/2)) of PP and PP/LDH hybrids describes overall crystallization behavior. The crystallite size (D(hkl)) and distribution of different crystallites in PP varied in presence of LDH. A significant increase in melting temperature is observed for PP/LDH hybrids. The POM showed that smaller and less perfect crystals were formed in nanocomposites because of molecular interaction between PP chains and LDH. The value of fold surface free energy (sigma(e)) of PP chains decreased with increasing LDH content. Finally, the overall results signify that LDH at nanometer level acted as nucleating agent and accelerate the overall crystallization process of PR (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Isothermal crystallization; Layered double hydroxide; Melting behavior; Polypropylene nanocomposites